"The surprising involvement of the outsider" : an examination of pessimism and Schopenhauerian ethics in J. M. Coetzee's Waiting for the Barbarians and Joseph Conrad's Under Western Eyes - Bosman, Sean James (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2017)
When the Swedish Academy lauded J. M. Coetzee for portraying situations in which "the distinction between right and wrong, while crystal clear, can be seen to serve no end" ("PR" para. 3), it presented an interpretation of his texts that considers ethics to be legislative and imperative (see Cartwright, NS 255). The Swedish Academy's assertions are worth exploring, given that this highly respected body's statements are indicative of the critical debates generated by Coetzee's work. It identified a common metaphysical malaise between Coetzee's Waiting for the Barbarians and Conrad's Under Western Eyes, and offered pessimism as a dubious explanation for this apparent lack of value in choosing between right and wrong action. This thesis takes exception to the logical inconsistencies of this opinion and offers a sustained and systematic counterargument with the aim of suggesting an alternative interpretation of the value of ethical action in the two works. My counterargument uses interpretive and methodological models that draw on the works of Gabriele Helms, cultural narratology and Bakhtinian theory in order to investigate the texts, using the philosophy of one of the foremost German pessimists, Arthur Schopenhauer, as an ideological point of reference. The affinity between Schopenhauerian philosophy and Eastern religions (particularly Brahmanism and Buddhism) suggests, contrary to the implications of the Swedish Academy's statements, that there is value in ethical and moral choices in systems other than those that posit Judeo-Christian rewards and punishments in an afterlife, and that pessimism cannot legitimately be used to nullify this value. Rather, UWE and WB present an alternative set of ethics - one that is voluntary and virtue-based, valuing acts of compassion above all else. But basing my arguments on the novels' textual affinities with Schopenhauerian ethics, I maintain that neither Conrad nor Coetzee offers strictly uncomplicated presentations of the value of compassion. Yet the sustained thematic and authorial considerations of compassionate deeds suggest that there is indeed value in deciding between morally right and morally wrong action - even if the 'rewards' are not guaranteed and may only - at best - be temporary.
Keywords: Coetzee, J. M., 1940- -- Waiting for the barbarians; Conrad, Joseph, 1857-1924 -- Under Western eyes; Schopenhauer, Arthur, 1788-1860; Ethics in literature; Outsiders in literature; Svenska akademien